BRIDGE RE-DESIGN CLASS A COMPOSITE GIRDER (GIRDER BRIDGE CASE STUDY OF COMPOSITE CLASS C+) RANTAU BAKULA BANJAR DISTRICT - Riyan Noor Cahyo; Syahril Taufik (Universitas Lambung Mangkurat, 2019)
In Rantau Bakula village are its main bridge girder composite construction. Due to the condition of the existing bridge is felt not designed for vehicles with a large payload then re-design bridge girder composite with spans of 25 m and 9 m wide bridge.In this planning will be carried out load analyzes include: self weight, additional dead load (weight of asphalt and rainwater), load lane